2022
DOI: 10.1155/2022/7140552
|View full text |Cite|
|
Sign up to set email alerts
|

Manta Ray Foraging Optimization with Vector Quantization Based Microarray Image Compression Technique

Abstract: DNA microarray technologies enable the analysis of the expression of numerous genes in an individual experiment and become an important approach in the field of medicine and biology for investing genetic function, regulation, and interaction. Microarray images can be investigated well for obtaining the contained genetic data. But is it undesirable to retain the genetic data and avoid the microarray images? Due to considerable attention to DNA microarray and several experiments being performed under distinct co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The approaches such as PSO, BA, and FA that were described were superseded by the superior compression capabilities of the system that was demonstrated. An MRFO employing an LBG-related microarray image compression (MRFOLBG-MIC) technique is investigated by Alkhaldi et al [12]. In most cases, the LBG technique was used in order to construct a local optimal codebook for image compressions.…”
Section: Related Workmentioning
confidence: 99%
“…The approaches such as PSO, BA, and FA that were described were superseded by the superior compression capabilities of the system that was demonstrated. An MRFO employing an LBG-related microarray image compression (MRFOLBG-MIC) technique is investigated by Alkhaldi et al [12]. In most cases, the LBG technique was used in order to construct a local optimal codebook for image compressions.…”
Section: Related Workmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%